Computer Games in Education. [article]. - Mayer, Richard E.
Visionaries offer strong claims for the educational benefits of computer games, but there is a need to test those claims with rigorous scientific research and ground them in evidence-based theories of how people learn. Three genres of game research are (a) value-added research, which compares the learning outcomes of groups that learn academic material from playing a base version of a game to the outcomes of those playing the same game with one feature added; (b) cognitive consequences research, which compares improvements in cognitive skills of groups that play an off-the-shelf game to the skill improvements of those who engage in a control activity; and (c) media comparison research, which compares the learning outcomes of groups that learn academic material in a game to the outcomes of those who learn with conventional media. Value-added research suggests five promising features to include in educational computer games: modality, personalization, pretraining, coaching, and self-explanation. Cognitive consequences research suggests two promising approaches to cognitive training with computer games: using first-person shooter games to train perceptual attention skills and using spatial puzzle games to train two-dimensional mental rotation skills. Media comparison research suggests three promising areas where games may be more effective than conventional media: science, mathematics, and second-language learning. Future research is needed to pinpoint the cognitive, motivational, affective, and social processes that underlie learning with educational computer games. -- (from the author)